Can a pneumothorax break your heart? (Faculty of Medicine Universitas Indonesia, 2015)
Takotsubo cardiomyopathy or apical ballooning is a condition characterized by transitory left ventricular dysfunction, affecting commonly postmenopausal females after foregoing acute emotional or physical stress. We report a case of a 63 year old female presenting with severe dyspnea and right-sided secondary spontaneous pneumothorax, initially treated with tube thoracostomy. Despite the fact that pneumothorax resolved, shortness of breath persisted and due to ST-segment elevation and increased Troponin I levels, she was admitted to cardiac catheterization. A significant coronary stenosis was ruled out and the diagnosis of a Takotsubo cardiomyopathy was established. Electrocardiographic findings were normalized within three days and attributable to prolonged air leakage. A thoracoscopic apex resection followed by a partial parietal pleurectomy was performed. Although Takotsubo cardiomyopathy is a rare syndrome, it should always be considered as a potential cardiac complication of a pneumothorax.